Gas Phase Emitter Effect of Thulium within Ceramic Metal Halide Lamps in Dependence on Frequency. Issue 2 (February 2014) - Ruhrmann, C.; Depta, M.; Bergner, A.; Höbing, T.; Denissen, C.; Suijker, J.; Mentel, J.; Awakowicz, P.
Abstract The gas phase emitter effect within ceramic metal halide (CMH) lamps reduces the effective work function of the electrode material and, therewith, the electrode temperature. An investigation of the gas phase emitter effect of thulium (Tm) within CMH lamps seeded with Tm iodide (TmI3) is carried out. For this purpose, phase resolved images of the arc attachment and measurements of the electrode temperature, Tm atom and ion densities are performed in dependence on operating frequency by pyrometry and optical emission spectroscopy. Additionally, the influence of a sodium iodide (NaI) admixture is studied. The emitter effect is generated by means of a monolayer of Tm atoms on the electrode surface generated by a Tm ion current within the cathodic phase. It overlaps onto the anodic phase at higher frequencies of some hundreds of hertz. The reason is the finite life time of the monolayer, which is determined by the adsorption energy of Tm on the tungsten surface. Due to the low electric field strength in front of the anode and the mass inertia, the emitter ions and atoms remain in front of the anode. They retard the decay of the monolayer and with it the increase of the work function. Moreover, a comparison of a lamp seeded with TmI3 and sodium iodide (NaI) with a lamp seeded only with TmI3 illustrates a slight reduction of the electrode tip temperature caused by a higher Tm saturation vapour pressure and a higher Tm amount within the lamp filling. The influence of Na appears to be quite low. (© 2014 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)